Bibliometric Analysis of Sharia Hotel Development as Halal Tourism Accommodation - Haryanto, Eko (International Journal Of Tourism, 2023)
Abstract: Over the last few decades, the tourism sector has experienced rapid development. Along with the continued development of the tourism sector, the concepts of tourism development are also increasingly diverse, one of which is halal tourism. Indonesia as the largest Muslim country in the world is certainly a very big opportunity in implementing the concept of developing halal tourism. In addition, research on the theme of halal tourism and Sharia hotels has been carried out a lot. The last six years have been very historic for developing tourism both in Indonesia and the world. 2018 and 2019 were the peak years for tourism. Then 2020 – 2022 was a difficult period for tourism, due to the covid – 19 pandemic, while 2023 was the recovery period for the tourism sector after the covid-19 pandemic.Purpose: This research aims to explore the development of scientific publications in the field of tourism, especially halal tourism, as well as Sharia hotels as accommodation providers for Muslim tourists which have been carried out a lot in the last 6 years, between 2018 – 2023.Research methods: This study used descriptive qualitative research methods using the Publish or Perish (PoP) software to collect data, and VosViewer to map the research network.Result and Discussion: A total of 200 articles related to keywords were collected using the keywords "Halal Tourism" AND "Sharia Hotel", but only 189 articles matched the predetermined criteria. The research findings show that for the last 6 years, 2022 is the year with the highest number of publications, namely 52 articles. Meanwhile, the highest number of citations is 326 citations in 47 articles published throughout 2021. Meanwhile, the VosViewer mapping results show that 44 keyword items are most used by researchers, which are grouped into 5 clusters.Conclusions: Research with the theme of Halal tourism and Sharia hotels has been carried out in the last 6 years. Opportunities for research themes that can be carried out are those related to halal tourism management, halal tourism destinations, and sharia hotel management.